Sovereign Sukuk (SBSN) as An Instrument Of Islamic Public Finance: Financing Infrastructure Development In Morotai Island Regency - Susiyanti Naser; Syaifuddin Syaifuddin; Nirwan Umasugi; Abd. Rauf Wajo; Jasmin (Universitas Islam Darul 'ulum Lamongan, 2026)
Sovereign Sharia Securities (SBSN) have emerged as a strategic Islamic public finance instrument for supporting national infrastructure development, particularly in peripheral and border regions. This study examines the role of SBSN in financing the Sofi–Wayabula II road development project in Morotai Island Regency, an outermost region of Indonesia designated as both a National Tourism Strategic Area and a Special Economic Zone. Employing a qualitative descriptive approach, the study draws on in-depth interviews with key stakeholders, field observations, and analysis of official project documents and regulatory frameworks related to SBSN implementation. The findings indicate that SBSN play a significant role in ensuring sustainable and reliable project financing, enabling accelerated infrastructure delivery through multi-year contracts, and strengthening transparency and accountability in budget management. The Sofi–Wayabula II road project has contributed positively to regional connectivity, community mobility, and local economic activities, particularly in tourism and trade. Despite challenges related to geographical conditions, weather constraints, and logistical limitations, SBSN-based financing has proven effective in maintaining project continuity. This study highlights the importance of sovereign sukuk as a viable Islamic financing instrument for promoting equitable infrastructure development and supporting fiscal stability in developing economies.